2019
DOI: 10.1155/2019/8650845
|View full text |Cite
|
Sign up to set email alerts
|

Speeding Violation Type Prediction Based on Decision Tree Method: A Case Study in Wujiang, China

Abstract: The speeding violation has become a key concern in the traffic safety management, as it increases the risk of traffic crashes, as well as the severity of these crashes. This uncivilized phenomenon is prominent and presents an increasing trend in Wujiang in recent years, which severely endangers the road traffic safety. This study is approved by the Traffic Police Brigade of Wujiang Public Security Bureau and aims to explore the characteristic of the speeding violation behaviour and attempt to make an effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…It primarily uses computer image processing technology and communication technology and obtains illegal vehicle information through an automatic detection device. It can regulate driving behaviors and ensure road traffic safety [9][10][11][12][13]. Some scholars have studied the effect of traffic violation monitoring on driving behaviors and vehicle speed.…”
Section: Introductionmentioning
confidence: 99%
“…It primarily uses computer image processing technology and communication technology and obtains illegal vehicle information through an automatic detection device. It can regulate driving behaviors and ensure road traffic safety [9][10][11][12][13]. Some scholars have studied the effect of traffic violation monitoring on driving behaviors and vehicle speed.…”
Section: Introductionmentioning
confidence: 99%
“…Several limitations of the current paper should be presented. First, this study fails to consider some significant factors identified by earlier speeding researches, such as drivers’ information [ 40 ], vehicle types [ 41 ], and weather [ 42 ]. Due to the limitation of GPS trajectory data, the specific information above cannot be obtained directly.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al's [7] research results show that the speeding violation level tends to occur in high rainfall environments. The foreign license plate and autumn present a larger probability of high speeding violation levels than the local license plate and other seasons (i.e., spring, summer, and winter), respectively.…”
Section: Introductionmentioning
confidence: 98%